Computarised Brain Tomography in Patients With Schizophrenia - Prieto-Rincón, Dexy; Angela Montiel, María; Bonilla, Ernesto; Piñerúa, Lorena; Mora, Eduardo; Siciliano, Silvia (Investigación Clínica, 2009)
We carried out brain tomography of 27 patients with schizophrenia and 17 normal control subjects. DSM-IV criteria were used for diagnosis. The parameters studied were: brain volume, lateral and third ventricles, brain surface and brain indexes. Previously the patients were evaluated with the following clinical scales: Positive and Negative Syndrome Scale (PANSS), Brief Psychiatric Rating Scale (BPRS), Global Assessment of Functioning Scale (GAF) and the GRAFFAR scale to evaluate cultural and socioeconomical levels. We detected an increase in the right and left lateral ventricles: brain ratios, an increase in the width of Sylvian fissures and in the third ventricle index. We did not find differences that could be related to sex or to a familial history of mental disease. No differences were observed in the group receiving medication when compared witn the group of untreated patients